Effect of chewing gum on bowel recovery following caesarean section: a randomized controlled trial - R., Gayathri; Sagili, Haritha; G., Rajagopalan; T. P., Elamurugan (International Surgery Journal, 2020)
Background: Postoperative ileus is the most frequent complication of any abdominal surgery. In case of patients who under caesarean sections it adds to the prolonged hospital stay and morbidity. Chewing gum acts similar to sham feeding has been proven to hasten return of gastrointestinal motility in non-obstetric abdominal surgery. To study the effectiveness of chewing gum on recovery of bowel function following Caesarean section. Methods: This study, a randomized controlled trial was conducted in the Department of Obstetrics and Gynecology, JIPMER over a period of 2 months. Age, parity and details of patients who underwent caesarean section (type/indication/duration) were noted. They were randomised and allocated into two groups, group a (gum chewing group) and group B (control group). Using a verbal questionnaire time of first feeling of hunger, first passage of flatus and first passage of feces were noted. Results: Mean time of first passage of flatus in group 1 (gum chewing) was 16.04±5.7 as compared to 22.05±4.8 in group 2 (standard care) and the difference was found to be statistically significant (p<0.01). Mean time of first passage of feces in group 1(gum chewing) was 27.08±3.2 as compared to 32.04±4.3 in group 2 (standard care). None of the patients in our study had any side effects with use of chewing gum. Conclusions: Chewing gum significantly improves bowel motility when administered to patients following caesarean section and may help.